Effects of Acute Interval Exercise on Arterial Stiffness and Cardiovascular Autonomic Regulatory Responses: A Narrative Review of Potential Impacts of Aging - Liu, Wei-Long; Lin, Yi-Yuan; Mündel, Toby; Chou, Chun-Chung; Liao, Yi-Hung (Frontiers in Cardiovascular Medicine, 2022)
The physiological changes associated with aging deleteriously impact cardiovascular function and regulation and therefore increase the risk of developing cardiovascular disease. There is substantial evidence that changes in the autonomic nervous system and arterial stiffness play an important role in the development of cardiovascular disease during the aging process. Exercise is known to be effective in improving autonomic regulation and arterial vascular compliance, but differences in the type and intensity of exercise can have varying degrees of impact on vascular regulatory responses and autonomic function. There is still little evidence on whether there are differences in the response of exercise interventions to cardiovascular modulatory effects across the lifespan. In addition, acute interval exercise challenges can improve autonomic modulation, although the results of interval exercise on autonomic physiological parameters vary. Therefore, this narrative review focuses on evaluating the effects of acute interval exercise on blood pressure regulation and autonomic responses and also incorporates studies investigating different age groups to evaluate the effects of acute interval exercise on the autonomic nervous system. Herein we also summarize existing literature examining the acute cardiovascular responses to varied modes of interval exercise, as well as to further compare the benefits of interval exercise with other types of exercise on autonomic regulation and arterial stiffness. After reviewing the existing literature, it has been shown that with advancing age, changes in the autonomic nervous activity of interval exercise result in significant impacts on the cardiovascular system. We document that with advancing age, changes in the autonomic nerves lead to aging of the nervous system, thereby affecting the regulation of blood pressure. According to the limited literature, interval exercise is more effective in attenuating arterial stiffness than continuous exercise, but the difference in exercise benefits may depend on the training mode, intensity, duration of exercise, and the age of participants. Therefore, the benefits of interval exercise on autonomic and arterial stiffness improvement still warrant investigation, particularly the impact of age, in future research.